A prospective study to compare levonogestrol intrauterine system and trans-cervical resection of endometrium for treatment of abnormal uterine bleeding - Hol, Kishorkumar V.; Shastri, Shraddha S.; Magar, Shilpa S.; Darawade, Sameer P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: This article is a study comparing the two most accepted forms of treatment for abnormal uterine bleeding - levonorgestrol intrauterine treatment and transcervical resection of endometrium, with regards to its acceptability, efficacy, adverse effects and user satisfaction. Aim of this study was to compare the acceptability, efficacy, adverse effects and user satisfaction of LNG-IUS and TCRE for treatment for AUB. Methods: A prospective observational study conducted in SKNMC and GH. Forty-nine women with abnormal uterine bleeding after hysteroscopic evaluation were included in this study; where 17 opted for LNG-IUS; 32 opted for TCRE with bipolar electrode. 15 patients in LNG-IUS group and 28 pts in TCRE group completed follow up. Menstrual pattern, pictorial blood loss assessment chart score, adverse effects, acceptability, satisfaction and reason for discontinuation were recorded at 6 weeks, 6 months and 12 months after the procedure. Prior to LNG-IUS insertion or endometrial ablation, endometrial and cervical pathology were excluded by D and C and cervical smear, respectively. TVUS was used to exclude possible causes of menorrhagia, including myomas and endometrial polyp as well as adnexal pathology. LNG-IUS insertion was performed as an office procedure one day after cessation of menstrual bleeding with a negative urine pregnancy test. Results: Menstrual blood loss reductions in TCRE and LNG-IUS groups were by 85.7% and 87.6% respectively after a year. Amenorrhoea was more common in TCRE group while spotting and systemic effects were more common in LNG-IUS group. Satisfaction and acceptance rates are higher in TCRE group. Conclusions: The TCRE and LNG-IUS are equally effective in reducing bleeding in AUB patients. Acceptance and satisfaction are better with TCRE, as a modality of treatment for AUB.